Dismantling democratic states - Suleiman, Ezra N., 1941- (Princeton University Press, 2005)
This text offers a corrective to the view that bureaucracy is the source of democracy's ills. It argues that 'government reinvention' has limited bureaucracy's capacity to adequately serve the public good.